Quantitative Calculation of the Clustering Behavior of Fe‐Rich and Cr‐Rich REFepCr1−pO3 Crystals. Issue 12 (21st September 2022) - Mo, Jiajun; Liu, Lebin; Zhang, Qinghang; Liu, Peijia; Xia, Yanfang; Liu, Min
Abstract : This work has focused on the cluster state of B‐site ions in the rare‐earth perovskite REFep Cr1−p O3, and GdFe0.5 Cr0.5 O3 is taken for instance. This analysis indicates a paramagnetic behavior of the system, which originates from the paramagnetic contribution of the Gd 3+ . An internal‐field model is used to simplify the superexchange interaction between the A/B‐sites. Furthermore, the cluster state of B‐site ions is computed using the average number of nearest‐neighborhoods. Using Marine Predator Algorithm to fit the experiment data, it is found that Fe–Cr interaction does not conform to the case of ferromagnetic superexchange; therefore, there is no spin glass behavior in this system. Via fitting the Mossbauer spectrum at low temperatures (120 and 12 K), the calculations described above are verified. The calculation gives the hyperfine‐field intervals Δ H of 2.47 and 0.92 T at 120 and 12 K. It is found that B‐site ions tend to form clusters. The arrangement of the ions is random and without the tendency of orderly interval occupation of ions (like double perovskite). The study sheds light on the mechanism of single‐ion clustering and introduces new methods for calculating single‐ion clustering states. It can also be applied to the case of other A‐site ions in perovskite system and is not just limited to p  = 0.5 in REBp B'1−p O3 . Abstract : This work determines the first calculation of the cluster state of the perovskite REFe1− x Cr x O3 system based on magnetic calculations using molecular field theory, using GdFe0.5 Cr0.5 O3 as an example, and the calculations show that the system has some Fe‐ and Cr‐rich cluster behavior. The calculated results are verified by the Mossbauer spectra.